Manipulus Guttiferarum, I. Caraipa pilosa (Calophyllaceae), a new species from the Parú massif, Venezuelan Guayana - Grande Allende, José Ramón; Cabral, Fernanda Nunes (Phytotaxa, 2016)
In this paper we describe and illustrate Caraipa pilosa, a new species from the Venezuelan Guayana endemic to the Parú massif, morphologically similar to C. aracaensis, a species endemic to Serra do Aracá in Amazonas, Brazil. These two species have similar leaf type (conspicuously coriaceous, the margins revolute and with conspicuous pubescence on the abaxial leaf surface), but in Caraipa pilosa the trichomes are longer (≤1 mm) than in C. aracaensis (≤0.1 mm) and present in young stems, upper leaf surface (especially in young leaves), inflorescence axes, sepals, ovaries, and fruits. Also, in Carapia pilosa, leaf blades are consistently larger than in C. aracaensis. Caraipa pilosa is only known from the montane forest of Cerro Parú, and its conservation status is Least Concern (LC, following the IUCN Red List categories).